Comparative analysis of bacterial communities in the sediment and seawater environments from marine large yellow croaker cages (Zhejiang coast, China) - Li, Tiejun; Guo, Dengkang; Shen, Yuan; Bao, Jingjiao; Jin, Lei (Frontiers in Marine Science, 2022)
Bacterial community plays a vital role in the open-oceanic aquaculture ecosystem, and its stability is crucial for maintaining the health of mariculture fish. However, there are no reported studies on microbial communities in the culture environment of marine fish cages. In this study, bacterial community composition and diversity of seawater and sediment habitats from 5 large yellow croaker cage farms were first investigated by 16S rRNA-based high-throughput sequencing. The composition of bacterial communities was visualized at the phylum and genus levels. Meanwhile, biological and ecological functions were also predicted. The bacterial diversity observed at 3 inshore sampling sites was higher in seawater groups than that in sediment groups. The alpha diversity indices were influenced by the geographic location, especially the inshore site Yueqing (YQ), showing higher values than other sampling sites. The pathogenic bacteria were prevalent in the aquaculture environments, and probiotics showed a relatively low proportion by comparing the potential pathogens. Our study provides baseline data on bacterial communities and diversity in the open-oceanic environments of cage-culture large yellow croaker.